Ln(x+7)+ln(x)=ln(18)

Simple and best practice solution for Ln(x+7)+ln(x)=ln(18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(x+7)+ln(x)=ln(18) equation:


Simplifying
Ln(x + 7) + ln(x) = ln(18)

Reorder the terms:
nL(7 + x) + ln(x) = ln(18)
(7 * nL + x * nL) + ln(x) = ln(18)
(7nL + nxL) + ln(x) = ln(18)

Multiply ln * x
7nL + nxL + lnx = ln(18)

Reorder the terms:
lnx + 7nL + nxL = ln(18)

Reorder the terms for easier multiplication:
lnx + 7nL + nxL = 18ln

Solving
lnx + 7nL + nxL = 18ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-18ln' to each side of the equation.
lnx + 7nL + -18ln + nxL = 18ln + -18ln

Reorder the terms:
-18ln + lnx + 7nL + nxL = 18ln + -18ln

Combine like terms: 18ln + -18ln = 0
-18ln + lnx + 7nL + nxL = 0

Add '-7nL' to each side of the equation.
-18ln + lnx + 7nL + -7nL + nxL = 0 + -7nL

Combine like terms: 7nL + -7nL = 0
-18ln + lnx + 0 + nxL = 0 + -7nL
-18ln + lnx + nxL = 0 + -7nL
Remove the zero:
-18ln + lnx + nxL = -7nL

Add '-1nxL' to each side of the equation.
-18ln + lnx + nxL + -1nxL = -7nL + -1nxL

Combine like terms: nxL + -1nxL = 0
-18ln + lnx + 0 = -7nL + -1nxL
-18ln + lnx = -7nL + -1nxL

Reorder the terms:
-18ln + lnx + 7nL + nxL = -7nL + 7nL + -1nxL + nxL

Combine like terms: -7nL + 7nL = 0
-18ln + lnx + 7nL + nxL = 0 + -1nxL + nxL
-18ln + lnx + 7nL + nxL = -1nxL + nxL

Combine like terms: -1nxL + nxL = 0
-18ln + lnx + 7nL + nxL = 0

Factor out the Greatest Common Factor (GCF), 'n'.
n(-18l + lx + 7L + xL) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing l to the left, all other terms to the right. Add '-1n' to each side of the equation. n + -1n = 0 + -1n Remove the zero: 0 = -1n Simplifying 0 = -1n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-18l + lx + 7L + xL)' equal to zero and attempt to solve: Simplifying -18l + lx + 7L + xL = 0 Reorder the terms: 7L + -18l + lx + xL = 0 Solving 7L + -18l + lx + xL = 0 Move all terms containing l to the left, all other terms to the right. Add '-7L' to each side of the equation. 7L + -18l + lx + -7L + xL = 0 + -7L Reorder the terms: 7L + -7L + -18l + lx + xL = 0 + -7L Combine like terms: 7L + -7L = 0 0 + -18l + lx + xL = 0 + -7L -18l + lx + xL = 0 + -7L Remove the zero: -18l + lx + xL = -7L Add '-1xL' to each side of the equation. -18l + lx + xL + -1xL = -7L + -1xL Combine like terms: xL + -1xL = 0 -18l + lx + 0 = -7L + -1xL -18l + lx = -7L + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -84=-4(3-4n)+2n | | 2(c-14)=37 | | 41=3x+25 | | z-9/-2=-3 | | t-22=14 | | 3r-6=6-r | | 3000/450 | | -.15x=60 | | -26=x/4=9 | | K^2-10k-30=0 | | g+4g-3=12 | | -2v+1+2v=-7+v | | -26=x/4 | | -(x-4)=2x-7 | | -16+19q=20q | | (-2/3)x=-4/3 | | 2c+-3c=2 | | -(x+3)=9 | | 2x=19/5=3 | | 4m-3-4n=11 | | -15c+-10c+-10=-10 | | 8+6p=8+6p | | y-10=29 | | 8x-5x=30 | | 8/24=2/n | | 3(k+13)-17=-2 | | n=5p+28+4 | | 3(z+3)=7+3z-6z | | -2(2k-5)=10 | | -19=13-8y | | 3f-8=10f+9-8f | | y^4-3y^2-2y=0 |

Equations solver categories